Assessment of Waste Treatment in Urbanized Areas in the Environmental Policy Context: National Experience - Kobylynska, T.; Motuzka, O. (Public Policy and Accounting, 2021)
The environmental challenges of today worsen the life conditions and create threats for a human. An issue of special concern in the environmental security context are urbanized areas characterized by heavy environmental pollution. Analysis of the impact of waste generation and treatment in Ukraine on the environmental performance of urbanized areas and its conformity with the principles for decision-making on setting priorities and strategies on the basis of comparable information has significant importance in elaborating urgent measures for environmental stabilization in urbanized areas. Principal component analysis was used for estimating the correlations between the factors of pollution in urbanized areas, their meaningful interpretation and modeling of the complex factor impact. The factors were selected, characterizing the environmental effects, which is waste generation from economic activities of stationary pollution sources in urbanized areas: burnt waste of all the hazard categories; total accumulated waste per 1 square km; capital investment and current expenses on treatment of waste of I–III hazard categories; capital investment and current expenses on treatment of waste of IV hazard category; capital investment and current expenses on waste disposal in specially designated places or waste objects of waste of ІV hazard category; capital investment and current expenses on monitoring and laboratory tests for the objective: waste treatment (except for radioactive waste). The results of assessment confirmed the impact of these factors on the environmental performance of Ukrainian cities.